J.D. Salinger : a life - Slawenski, Kenneth (Random House, 2010)
One of the most popular and mysterious figures in American literary history, J.D. Salinger eluded fans and journalists for most of his life. Filled with new information and revelations, garnered from countless interviews, letters, and public records, this biography presents his extraordinary life that spanned nearly the entire twentieth century. The author explores Salinger's privileged youth, revealing the brilliant, sarcastic, vulnerable son of a disapproving father and doting mother and his entrance into a social world where Gloria Vanderbilt dismissively referred to him as a Jewish boy from New York. Here too are accounts of Salinger's first broken heart (Eugene O'Neill's daughter, Oona, left him for the much older Charlie Chaplin) and the devastating World War II service of which he never spoke and which haunted him forever. Whether it is revealing the facts of his hasty, short lived first marriage or his lifelong commitment to Eastern religion, which would dictate his attitudes toward sex, nutrition, solitude, and creativity, this biography is Salinger's unforgettable story in full.